THE IMPORTANCE OF ONLINE COMMUNICATION IN HIGHER EDUCATION - Emanuela Maria AVRAM (Network Intelligence Studies, 2015)

(untitled)
The communication system is highly developed in the academic environment and not only involves the communication between the university and the outside world through exchanges of messages, but also the internal one with the employees and students. Online communication has gained increasingly more territory in the academic environment lately, especially thanks to the usage of e-mails and social networks. Therefore, this paper aims at presenting the main tools of the online communication in higher education as well as their importance of creating interaction among the participants in the education process. The conclusions emphasize that this type of communication significantly favors the teaching-learning process, creates real interaction between students and professors and contributes to the fast dissemination and access of information.